SUBSITUSI TEPUUNG TERIGU DENGAN UBI UNGU KUKUS PADA PEMBUATAN KUE BINGKE - hartono, Hartono (Fakultas Pertanian Universitas Tanjungpura, 2019)
This research aims to find the best substitution of wheat flour with steamed purple sweet potato in the making of bingke cake and to obtain purple bingke composition that is most liked by consumers. This study used a randomized block design (RBD) of one factor, that was the ratio of formulation between wheat flour and steamed purple sweet potato repeated 4 times with 6 levels. The observed parameters were water content, total dissolved solids (TDS), protein content, and sensory. The data obtained were analyzed using ANOVA with 5% significance, with further testing using Duncan